2021
DOI: 10.1063/5.0065348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of velocity shear layer on detonation propagation in a supersonic expanding combustor

Abstract: This study investigates the mechanism of detonation propagation in a stoichiometric hydrogen-oxygen mixture with non-uniform flow velocity entering an expanding combustor. For simulation of the detonation propagation, the Navier-Stokes equations with a one-step two-species chemistry model are solved by employing the hybrid sixth-order weighted essentially non-oscillatory centre difference scheme. The self-sustaining mechanism of detonation propagation in an expanding combustor under the action of non-uniform s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 64 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…The interaction of the vortex formed by the dual jet in the static air flow field and the combustion front enhances the intensity of the turbulence, which contributes significantly to the detonation process [18]. To accurately simulate small-scale flow details such as turbulence and vortices, the two-dimensional Navier-Stokes equation is adopted as the governing equation [29].…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…The interaction of the vortex formed by the dual jet in the static air flow field and the combustion front enhances the intensity of the turbulence, which contributes significantly to the detonation process [18]. To accurately simulate small-scale flow details such as turbulence and vortices, the two-dimensional Navier-Stokes equation is adopted as the governing equation [29].…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…In uniform supersonic flows, experimental analyses demonstrated that the propagation speed of the leading detonation wave in straight tubes is closely related to the ratio of the height occupied by the detonation wave to the height of the duct [8]. While in nonuniform supersonic flows, the self-sustaining mechanism of the detonation propagation becomes more complicated owing to the interaction with a velocity shear layer [9]. Since the combustion mechanisms in the mainstream and boundary layers are totally different owing to shock bifurcations and boundary limit, it is of great importance to distinguish the combustion modes/propagation modes of the detonation wave in the DWBLI [38][39][40].…”
Section: Takedown Policymentioning
confidence: 99%
“…Researchers have looked into various aspects of scramjet combustion phenomena. These include the mechanism of detonation propagation; shock impingement at the inlet; flame acceleration and deflagration to detonation transition; solid-fueled scramjets; supersonic hydrogen jet in a crossflow configuration; computational analysis of high-speed combustors, such as HyShot II and the DLR experimental rig, and staggered ramp and strut injector configurations [4][5][6][7][8][9][10][11] . Due to the extreme flow environment, experimental measurements are difficult to be obtained and encompass many uncertainties.…”
Section: Introductionmentioning
confidence: 99%